Strategi untuk Meningkatkan Kesadaran Masyarakat Mengenai Perawatan dan Pengaktifan Masjid di Desa Gunung Agung - Andri Frediansyah; Ayub Muzaki Nur; Puspa Yuni Rahayu; Delia Helmanita; Siti Nur Azizah; Siti Zahara; Septi Puspitasari; Jelsa Febriani; Edwin Porwanto; Dwi Permatasari; Khosi’in (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This research aims to raise public awareness about the maintenance and activation of mosques, identify the issues at Nurul Ihsan Mosque, and carry out a community service program to enhance religious and social activities in the village. The research was conducted by students of KKN Group 109, Batch 3, from Fatmawati Sukarno Islamic University Bengkulu, during the even semester of the 2023/2024 academic year. The research method used was observation and analysis of primary data from village informants, the implementation of a mosque-based community service program over 40 days, including Iqra guidance, religious studies, and social activities such as elderly exercise and the creation of a mosque garden. The results of the research indicate an increased interest among children in religious activities, a shift in sermon topics from theology to community empowerment, and enhanced religious knowledge and awareness of the importance of instilling religious values in children.